Koreksi Tanggal Wafat Umar Bin Khattab dalam Perspektif Astronomi - Akhmad Nadirin; Ahmad Izzuddin (University of Muhammadiyah Sumatera Utara, 2022)
Umar bin Khattab was a friend of the Prophet Muhammad SAW who had the title Amirul Mukminin. He led Islam for about 10 years before being stabbed by Abu Lu'luah while in the morning prayers at the end of the 23rd year until his death. There are many opinions in Islamic historical literature about the death of Umar bin Khattab. Some say 3, 4 or 7 days left in Dzulhijjah 23 H or the bieginning of Muharram 24 H. This study is intended for the first, knowing why there is a difference in death data, the second answers to the problem of correction of the death data of Umar bin Khattab in an astronomical perspective. These problems are discussed with qualitative research in the form of library research. The primary sources used in this study are, Tarikh al-Tabari Tarikh al-Umam wa al-Muluk, Ashab al-Futuya , al-Kamil fi al-Tarikh, Siyar Alam al-Nubula, al-Bidayah wa al-Nihayah All data obtained is then converted both into days and dates and matched the suitability of the data. The results of the research show that the death data of Umar bin Khattab based on astronomical calculations is on Wednesday, three days left in the month of Dzulhijjah 23 H which coincides with the 26th of Dzulhijjah 23 H / 3 November 644 AD",